A. \(xy' - 1 = - {e^y}\)
B. \(xy' + 1 = - {e^y}\)
C. \(xy' - 1 = {e^y}\)
D. \(xy' + 1 = {e^y}\)
D
Ta có: \(y = \ln \frac{1}{{x + 1}} = \ln 1 - \ln \left( {x + 1} \right) = - \ln \left( {x + 1} \right)\)
Suy ra \(y' = \left[ { - \ln \left( {x + 1} \right)} \right]' = - \frac{{\left( {x + 1} \right)'}}{{x + 1}} = - \frac{1}{{x + 1}}\)
Do đó \(xy' - 1 = x.\left( { - \frac{1}{{x + 1}}} \right) - 1 = \frac{{ - x - \left( {x + 1} \right)}}{{x + 1}} = \frac{{ - 2x - 1}}{{x + 1}}\).
\(xy' + 1 = x.\left( { - \frac{1}{{x + 1}}} \right) + 1 = \frac{{ - x + \left( {x + 1} \right)}}{{x + 1}} = \frac{1}{{x + 1}}\).
\({e^y} = {e^{ - \ln \left( {x + 1} \right)}} = {e^{\ln \frac{1}{{x + 1}}}} = \frac{1}{{x + 1}} = xy' + 1\).
Vậy \(xy' + 1 = {e^y}\).
Chọn D.
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247